General anesthesia vs. non-general anesthesia for vertebrobasilar stroke endovascular therapy - Lu, Yanan; Xu, Pengfei; Wang, Jinjing; Xiao, Lulu; Zhang, Pan; Duan, Zuowei; Liu, Dezhi; Liu, Chaolai; Wang, Delong; Wang, Di; Zhang, Chao; Yao, Tao; et al. (Frontiers in Neurology, 2023)
Abstract Background The optimal type of anesthesia for acute vertebrobasilar artery occlusion (VBAO) remains controversial. We aimed to assess the influence of anesthetic management on the outcomes in VBAO patients received endovascular treatment (EVT). Methods Patients underwent EVT for acute VBAO at 21 stroke centers in China were retrospectively enrolled and compared between the general anesthesia (GA) group and non-GA group. The primary outcome was the favorable outcome, defined as a modified Rankin Scale (mRS) score 0–3 at 90 days. Secondary outcomes included functional independence (90-day mRS score 0–2), and the rate of successful reperfusion. The safety outcomes included all-cause mortality at 90 days, the occurrence of any procedural complication, and the rate of symptomatic intracranial hemorrhage (sICH). In addition, we performed analyses of the outcomes in subgroups that were defined by Glasgow Coma Scale (GCS) score (≤ 8 or > 8). Results In the propensity score matched cohort, there were no difference in the primary outcome, secondary outcomes and safety outcomes between the two groups. Among patients with a GCS score of 8 or less, the proportion of successful reperfusion was significantly higher in the GA group than the non-GA group (aOR, 3.57, 95% CI, 1.06 to 12.50, p = 0.04). In the inverse probability of treatment weighting-propensity score-adjusted cohort, similar results were found. Conclusions Patients placed under GA during EVT for VBAO appear to be as effective and safe as non-GA. Furthermore, GA might yield better successful reperfusion for worse presenting GCS score (≤ 8).